Emotional expressions of old faces are perceived as more positive and less negative than young faces in young adults - Hass, Norah C.; Schneider, Erik J. S.; Lim, Seung-Lark (Frontiers in Psychology, 2015)
Interpreting the emotions of others through their facial expressions can provide important social information, yet the way in which we judge an emotion is subject to psychosocial factors. We hypothesized that the age of a face would bias how the emotional expressions are judged, with older faces generally more likely to be viewed as having more positive and less negative expressions than younger faces. Using two-alternative forced-choice perceptual decision tasks, participants sorted young and old faces of which emotional expressions were gradually morphed into one of two categories - “neutral vs. happy” and “neutral vs. angry.” The results indicated that old faces were more frequently perceived as having a happy expression at the lower emotional intensity levels, and less frequently perceived as having an angry expression at the higher emotional intensity levels than younger faces in young adults. Critically, the perceptual decision threshold at which old faces were judged as happy was lower than for young faces, and higher for angry old faces compared to young faces. These findings suggest that the age of the face influences how its emotional expression is interpreted in social interactions.